Chemical composition, anti-toxoplasma, cytotoxicity, antioxidant, and anti-inflammatory potentials of Cola gigantea seed oil - O. Atolani; H. Oguntoye; E. T. Areh; O. S. Adeyemi; L. Kambizi (Taylor & Francis Group, 2019)
Context: Cola gigantea A. Chev. (Sterculiaceae) is an important medicinal tropical flora. Objective: The seed oil of C. gigantea, an underutilized tropical plant was investigated for its antioxidant, anti-inflammatory, anti-Toxoplasma, and cytotoxicity activities as well as the chemical composition. Materials and methods: The physicochemical parameters of the seed oil obtained via Soxhlet extraction was determined while the fatty acid and non-fatty acid component were analyzed by gas chromatography-mass spectrometry. The antioxidant activity was evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azino-bis-(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) assays (10-50 µg/mL) while the anti-inflammatory property was determined through Cell Membrane Stabilization assay. The anti-parasite and cytotoxicity activity were evaluated (0-1000 µg/mL) using Toxoplasma gondii and mammalian cell line assays, respectively. Results: The oil had fatty acids which ranged from C-12 to C-23 with linoleic (18:2) and palmitic acids (16:0) being dominant. The oil had 89.41% unsaturated fatty acids with sterolic acid, an uncommon acetylenic fatty acid reported for the first time. Non-fatty acids obtained include cholesterol (2.12%), campesterol (14.12%), stigmasterol (34.07%) and β-sitosterol (49.68%). The oil had a significantly (p < 0.05) low scavenging activity against DPPH radicals (IC50 > 50 µg/mL) compared with ascorbic acid. In contrast, the oil showed better activity against ABTS radicals (IC50 44.19 ± 6.27 µg/mL) compared with ascorbic acid or quercetin. Furthermore, the oil showed anti-T. gondii and dose-dependent cytotoxicity in HFF cells with selectivity index (IC50/EC50 < 1). Discussion and conclusions: The antioxidant potential of the oil suggests that it may serve as a potential source for various preparations for pharmaceuticals and cosmeceuticals.